CLINICAL CASE OF DIFFERENTIAL DIAGNOSIS OF HYPOGLYCEMIA SYNDROME - Епифанова, Елизавета Эдуардовна; Еленская, Татьяна Сергеевна; Павленко, Владимир Вячеславович; Каменева, Евгения Александровна; Кокоулина, Юлия Андреевна (Medicine in Kuzbass, 2024)
The article presents a clinical case of insulinoma, which is the most common, hormone-producing tumor of the pancreas, manifested by hyperinsulinemic hypoglycemia. The prevalence of insulinoma in the general population is estimated to be about
Keywords: insulinoma; hypoglycemic states; hormone-producing tumor